2020
DOI: 10.1002/mgg3.1268
|View full text |Cite
|
Sign up to set email alerts
|

Human closed and open apex premolar teeth express different toll‐like receptor

Abstract: BackgroundThe innate immune activation which promotes inflammation responses in the dental pulp tissue leads to the progression of dentin caries. Accordingly, toll‐like receptors (TLRs) are key molecules of the innate immune system that identify pathogen‐associated molecular patterns (PAMPs) on microorganisms and may have a critical role in a dental injury. Therefore, this study aimed to investigate the expression of TLR2, TLR3, and TLR4 in the human dental pulp of opened and closed apex teeth.MethodsHuman den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…TLR3 agonist (poly[I:C]) can augment the suppressive potential for T, B and NK cell responses of adult mesenchymal stem cells (MSCs) from dental pulp and dental follicle and potentiated TGF‐β and IL‐6 secretions by these cells (Tomic et al, 2011; Waterman et al, 2010). However, it has also been shown that TLR3 expression did not change significantly with apex formation and closure of the apical foramen, whilst TLR2 and TLR4 expression increased, which may be due to the presence of microorganisms in pulp tissue (Jafari et al, 2020).…”
Section: Endosomal Nucleic Acid Sensing (Na‐sensing Tlrs) In Endodont...mentioning
confidence: 99%
“…TLR3 agonist (poly[I:C]) can augment the suppressive potential for T, B and NK cell responses of adult mesenchymal stem cells (MSCs) from dental pulp and dental follicle and potentiated TGF‐β and IL‐6 secretions by these cells (Tomic et al, 2011; Waterman et al, 2010). However, it has also been shown that TLR3 expression did not change significantly with apex formation and closure of the apical foramen, whilst TLR2 and TLR4 expression increased, which may be due to the presence of microorganisms in pulp tissue (Jafari et al, 2020).…”
Section: Endosomal Nucleic Acid Sensing (Na‐sensing Tlrs) In Endodont...mentioning
confidence: 99%
“…This condition followed by disruption of cathepsin B and K and suppression of MMP-2/9 expression so the destruction process of the dentin and pulp is inhibited. [56][57][58][59][60][61][62][63][64][65][66][67][68] PA induces COL1A1 formation and cross-linking to dentin. COL1A1 is an organic material of dentin matrix.…”
Section: Pa Loaded Pamam-cp Nanoparticles As Pulp Cappingmentioning
confidence: 99%
“…Endodontic treatment planning of young permanent teeth is a challenging process and should be carried out with discretion [1][2][3], since they may have large root canal with thin dentinal walls, short roots, open apexes and, in most cases, extensive apical resorption [4][5][6][7][8][9][10]. These factors can have direct impact on biomechanical preparation, cleaning and disinfection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature has shown that the manual instruments used during the biomechanical preparation are incapable of touching all the large root canal walls. Moreover, they favour overinstrumentation when they are forcibly used against the thin walls, producing excessive wear with greater risk of deviations, perforations and root fractures, and increased risk of overinstrumentation [2, 3, 7–9, 10, 11, 14, 15], probably due to the large diameter, alloy composition and design of manual instruments.…”
Section: Introductionmentioning
confidence: 99%